2017
DOI: 10.1109/tmm.2016.2614880
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Analysis of Perceptual Multimedia Experience Based on Physiological Response: A Review

Abstract: The exponential growth of popularity of multimedia has led needs for user-centric adaptive applications that manage multimedia content more effectively. Implicit analysis, which examines users' perceptual experience of multimedia by monitoring physiological or behavioral cues, has potential to satisfy such demands. Particularly, physiological signals categorized into cerebral physiological signals (electroencephalography, functional magnetic resonance imaging, and functional nearinfrared spectroscopy) and peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 124 publications
0
12
0
1
Order By: Relevance
“…The objective measurements require observing the body response during stereoscopic perception of differently rendered stereoscopic images. The most widely used tools to follow the body response in the research field are eye-tracking devices (Bernhard et al 2014;Iatsun et al 2015;Lin, Kao 2018) and brain scanning devices (Fischmeister, Bauer 2006;Frey et al 2016;Moon, Lee 2017). However, other means to measure visual discomfort are also investigated, e.g., Lee et al 2016 showed it is possible to measure visual discomfort using facial expressions.…”
Section: Visual Fatigue and Visual Discomfortmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective measurements require observing the body response during stereoscopic perception of differently rendered stereoscopic images. The most widely used tools to follow the body response in the research field are eye-tracking devices (Bernhard et al 2014;Iatsun et al 2015;Lin, Kao 2018) and brain scanning devices (Fischmeister, Bauer 2006;Frey et al 2016;Moon, Lee 2017). However, other means to measure visual discomfort are also investigated, e.g., Lee et al 2016 showed it is possible to measure visual discomfort using facial expressions.…”
Section: Visual Fatigue and Visual Discomfortmentioning
confidence: 99%
“…Atliekant objektyvų vertinimą yra stebimas savanorių biologinis atsakas į rodomą turinį. Stebint biologinių signalų pokytį dažniausiai yra naudojama akių sekimo įranga (Bernhard et al 2014;Iatsun et al 2015;Lin, Kao 2018), bei smegenų aktyvumo matavimo įranga (Fischmeister, Bauer 2006;Frey et al 2016;Moon, Lee 2017). Žinoma, yra ieškoma ir kitų objektyvių būdų vertinti regos diskomfortą, savo tyrime, Lee et al 2016 parodė, kad regos diskomfortą galima vertinti remiantis veido išraiškomis.…”
Section: Literatūros šAltinių Apie Regos Diskomforto Radimą Metodų Apunclassified
“…Classification accuracy [7] Gaussian naive Bayes classifier leave-one-video-out for each subject 0.502 (F1-score) [14] Relevance vector machine leave-one-video-out for each subject 0.65 (F1-score) [15] Ensemble classifier* leave-one-trial-out 0.647 [16] Support vector machine leave-one-video-out for each subject 0.705 [17] Deep belief network five-fold cross-validation for each subject 0.867 (F1-score) [18] Recurrent neural network four-fold cross-validation 0.880 *Ensemble of support vector machine, nearest mean, 1-nearest neighbor, k-nearest neighbor, and linear discriminant analysis scaling for content delivery [12] and personalized multimedia recommendation [13]. A limitation of the existing EEG-based implicit QoE assessment systems is that their performance still remains at insufficient levels for real-world applications where high reliability is critical.…”
Section: Ref Classifier Classification Schemementioning
confidence: 99%
“…However, the results of NR metrics do not always have an ideal correlation with the perceived image quality. In general, subjective evaluation methods can be categorized into explicit and implicit approaches . Explicit evaluation methods are designed to achieve the subjective perception of participants while viewing the images in the specified experimental environment in the form of scoring.…”
Section: Introductionmentioning
confidence: 99%
“…In general, subjective evaluation methods can be categorized into explicit and implicit approaches. 13 Explicit evaluation methods are designed to achieve the subjective perception of participants while viewing the images in the specified experimental environment in the form of scoring. The ITU-R and ITU-T Recommendations have developed detailed information to conduct the explicit assessment experiments.…”
Section: Introductionmentioning
confidence: 99%